EFFECT OF FOLIAR APPLICATION OF CHELATED ZINC, GIBBERELLIC ACID GA3 AND KINETIN ON GROWTH OF ZAGHINIA APRICOT SEEDLINGS - Ameen, Nabil M.; Hussein, Luma Basher (Diyala Agricultural Sciences Journal, 2020)
Factorial experiment has been conducted on apricot transplants (Prunus armeniaca L.) cv. Zaghinia of the Department of Horticulture and Landscape Design, College of Agriculture and Forestry, University of Mosul, during the growing seasons 2008. To study the effect of foliar application of chelated zinc Zn-EDTA with three levels 0, 50 and 100 mgZn.l-1 , spray with two concentrations of Gibberellic acid 0 and 100 mg GA3.l-1 and spray with three concentrations of kinetin 0, 125 and 250mg KIN.l-1 and study the effects of interaction between all factors were studied on the growth and minerals content of Apricot seedlings. The results showed that foliar application of Zn-EDTA with 50mg.l-1 caused significant increase on the total chlorophyll, nitrogen, and potassium percentage in leaves. Significant increase obtained in phosphorus and zinc concentrations in the leaves on 100mgGA3.l-1. Spray with Gibberellic acid at 100mgGA3.l-1 caused significant increase in dry weight of roots, total chlorophyll, nitrogen, and phosphorus percentage in leaves. Spray with Kinetin at 125mgKIN.l-1 caused significant increase in nitrogen, phosphorus, potassium and zinc in the leaves. While Spray with 250mgKIN.l-1 caused significant increase in total of chlorophyll in the leaves. The results of triple interaction between all factors caused significant effect on dry weight of roots and total chlorophyll with 50mgZn.l-1 + 100mgGA3.l-1 + 250mgKIN.l-1.